North and South - Jakes, John (Harcourt Brace, 1982)
A panoramic novel of two wealthy famillies in the 20 turbulent years culminating in the Civil War. The Mains, plantation owners, proudly defending an aristocratic way of life and the Hazards, Pennsylvania industrialists, descended from an English fugitive and now caught up in the world of commerce and invention. When their two sons meet at West Point and become good friends, the lives of the families areirrevocably joined.
Keywords: War Fiction; Family Saga Fiction; Classic Literature & Fiction